2018
DOI: 10.1111/1753-0407.12836
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response association between the triglycerides: High‐density lipoprotein cholesterol ratio and type 2 diabetes mellitus risk: The rural Chinese cohort study and meta‐analysis

Abstract: The TG/HDL-C ratio was an independent risk factor of T2DM, especially in females, and linearly increased the risk of T2DM; thus, it may be a useful indicator to identify future T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
39
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 37 publications
6
39
1
Order By: Relevance
“…In Chinese population, He et al [7] found in a retrospective study of 687 adults in an urban community located in Chengdu, Sichuan province, China that TG/HDL-C was one of independent DM risk factors and they observed an increasing trend of T2DM risk with TG/HDL-C after adjusting for potential confounders. Another study [9] enrolled 10,741 rural Chinese has similar finding. Consistently the same result that, we obtained cox proportional hazard regression model showed a significant and strong association between TG/ HDL-C and incident of diabetes.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In Chinese population, He et al [7] found in a retrospective study of 687 adults in an urban community located in Chengdu, Sichuan province, China that TG/HDL-C was one of independent DM risk factors and they observed an increasing trend of T2DM risk with TG/HDL-C after adjusting for potential confounders. Another study [9] enrolled 10,741 rural Chinese has similar finding. Consistently the same result that, we obtained cox proportional hazard regression model showed a significant and strong association between TG/ HDL-C and incident of diabetes.…”
Section: Discussionsupporting
confidence: 60%
“…They showed positive association between TG/ HDL-C and diabetes [7][8][9][10], while one study reached inconsistent results [11]. In Chinese, two studies [7,9] found that TG/HDL-C independently increased the Type 2 diabetes (T2DM) risk in a general population, however, the relatively small sample size and regional population limited to generalizable other people. Therefore, this study set out to investigate whether TG/HDL-C was independently related to the risk of incident diabetes in a large cohort population across 32 sites and 11 cities in China.…”
Section: Introductionmentioning
confidence: 99%
“…In the current issue of the Journal, Cheng et al analyzed a cohort of 10 741 Chinese people followed for a median of 6 years, of whom 618 developed type 2 diabetes (T2D), assessing the usefulness of the triglyceride: high‐density lipoprotein cholesterol (TG/HDL‐C) ratio as a lipid marker of diabetes risk. A higher TG/HDL‐C ratio was associated with older age, female sex, smoking, drinking alcohol, hypertension, height, weight, waist circumference (WC), body mass index (BMI), systolic and diastolic blood pressure (SBP and DBP, respectively), and fasting plasma glucose (FPG).…”
mentioning
confidence: 99%
“…When adjusted for age, sex, education level, physical activity, smoking, alcohol use, BMI, SBP, DBP, FBG, total cholesterol, family history of T2D, and hypertension status, the risk ratio of the fourth versus first quartile of the TG/HDL‐C ratio was 2.11. Cheng et al performed a meta‐analysis of their and three other studies, comprising 20 302 non‐diabetic people and finding that for each 1‐unit increment in the TG/HDL‐C ratio, the likelihood of diabetes increased 1.28‐fold. Another analysis using the same dataset showed that, among people with initially normal FPG followed for 6 years, the product of WC with the TG/HDL‐C ratio, of TG with FPG, and of WC with TG levels tracked similarly but more strongly with T2D than the TG/HDL‐C ratio, with similar predictive strength to WC and FPG .…”
mentioning
confidence: 99%
See 1 more Smart Citation